2012
DOI: 10.1094/pdis-12-11-1058-re
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Venturia inaequalis Growth in Malus × domestica with Quantitative Real-Time Polymerase Chain Reaction

Abstract: Gusberti, M., Patocchi, A., Gessler, C, and Broggini, G. A. L. 2012. Quantification of Venturia inaequalis growth in Malus x domestica with quantitative real-time polymerase chain reaction. Plant Dis. 96:1791-1797.A quantitative real-time polymerase chain reaction (qPCR) was developed and validated for quantification of Venturia inaequalis in infected leaf tissue of Malus x domestica. The method is based on dual-labeled hybridization probes, allowing simuhaneous detection of host and pathogen DNA within one si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Colonization coefficient (ratio between pathogen and host DNA per leaf) calculated for the three investigated cisgenic lines C7.1.49, C11.1.53 and C12.1.49 measured by qPCR after Gusberti et al . () 21 days following inoculation with V. inaequalis . ‘Florina’ is a scab‐resistant Rvi6 ‐cultivar, while ‘Gala’ is the scab‐susceptible genotype used for generation of cisgenic lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonization coefficient (ratio between pathogen and host DNA per leaf) calculated for the three investigated cisgenic lines C7.1.49, C11.1.53 and C12.1.49 measured by qPCR after Gusberti et al . () 21 days following inoculation with V. inaequalis . ‘Florina’ is a scab‐resistant Rvi6 ‐cultivar, while ‘Gala’ is the scab‐susceptible genotype used for generation of cisgenic lines.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the low expression, partial resistance was observed in our lines: the results of qPCR quantification of the colonization coefficient (CCcorr, Figure ) indicated that the results obtained 21 dpi for ‘Gala’ and ‘Florina’ were similar to the ones reported by Gusberti et al . (). The cisgenic lines C7.1.49, C11.1.53 and C12.1.49 showed CCcorr values similar to those of ‘Milwa’, a moderately resistant cultivar (Gusberti et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…While such microscopic observations are labour intensive, the effort would be worthwhile for determining segregation of phenotypes in progeny populations for genetic mapping, but not for routine screening of seedling population. Alternatively, a recent report demonstrates the effectiveness of quantitative realtime polymerase chain reaction for detecting and quantifying the pathogen on leaf material and may serve as high-throughput tool for screening progeny (Gusberti et al, 2012). The classification of 'Honeycrisp' and its ancestors and progeny into several resistance classes is similar to the diverse responses observed in Rvi6, Rvi11 and Rvi12, which also range from 0 to 3b (Table 2).…”
Section: Discussionmentioning
confidence: 80%
“…This problem was evaded by using a two-step protocol for the latter amplicon as indicated in the resulting standard curve slope value (M=−3.6). In a recent study by Gusberti et al (2012) another gene (ABC2) was used for V. inaequalis-qPCR, which resulted in a 20 times lower detection limit of 1 × 10 −4 ngV. inaequalis DNA within leaf tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Speciesspecific amplification of V. inaequalis has been reported in literature using standard PCR protocols with primers to amplify the internal transcribed spacer (ITS) and the cytochrome 51A1 (CYP51A1) regions, respectively (Schnabel and Jones 2001;Stehmann et al 2001). The first report of qPCR for estimating V. inaequalis infection was published using the ITS region and the housekeeping genes ABC2 and EF1 (Daniëls et al 2012;Gusberti et al 2012). Determination of the efficiency of a sanitation treatment in reducing ascospore dose through molecular quantification has not previously been published and might represent a more accurate way to test for numbers of ascospores discharged and timing of this than microscopic analysis alone.…”
Section: Introductionmentioning
confidence: 99%